REDUÇÃO DE SÓLIDOS ORIUNDO DA CO-DIGESTÃO ANAERÓBIA DOS DEJETOS DE BUBALINOS E SUÍNOS - SANTOS, Marrony Gonçalves Pires dos,; BEZERRA, Thaís dos Santos2 (thaysantos09876@gmail.com),; CORREA, Jonas de Sousa,; SANTOS, Tânia Mara Baptista dos, (ANAIS DO ENIC, 2023)
-